UVB-Induced Senescence of Human Dermal Fibroblasts Involves Impairment of Proteasome and Enhanced Autophagic Activity. (11th August 2016) - Cavinato, Maria; Koziel, Rafal; Romani, Nikolaus; Weinmüllner, Regina; Jenewein, Brigitte; Hermann, Martin; Dubrac, Sandrine; Ratzinger, Gudrun; Grillari, Johannes; Schmuth, Matthias; Jansen-Dürr, Pidder
Abstract: In the current study, we have extended previous findings aiming at a better understanding of molecular mechanisms underlying UVB-induced senescence of diploid human dermal fibroblasts (HDFs), an experimental model to study the process of photoaging in the skin. We provide evidence that the inhibition of proteasomal degradation of damaged proteins and the activation of autophagosome formation are early events in UVB-induced senescence of HDFs, dependent on UVB-induced accumulation of reactive oxygen species. Our data suggest that autophagy is required for the establishment of the senescent phenotype in UVB-treated HDFs and that inhibition of autophagy is sufficient to change the cell fate from senescence to cell death by apoptosis. Studies in reconstructed skin equivalents revealed that UVB irradiation triggers hallmarks of autophagy induction in the dermal layer. These findings have potential implications for fundamental as well as translational research into skin aging, in particular photoaging.